2004
DOI: 10.4049/jimmunol.172.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: An Endogenous Pathway to Systemic Inflammatory Response Syndrome (SIRS)-Like Reactions through Toll-Like Receptor 4

Abstract: Systemic inflammatory response syndrome (SIRS) is typically associated with trauma, surgery, or acute pancreatitis. SIRS resembles sepsis, triggered by exogenous macromolecules such as LPS acting on Toll-like receptors. What triggers SIRS in the absence of infection, however, is unknown. In this study, we report that a SIRS-like response can be induced in mice by administration of soluble heparan sulfate, a glycosaminoglycan associated with nucleated cells and extracellular matrices, and by elastase, which cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
174
0
6

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(187 citation statements)
references
References 41 publications
7
174
0
6
Order By: Relevance
“…Moreover, in vivo TLRs can also be stimulated by factors liberated after cell necrosis, which is a frequent event in high-grade gliomas. Additionally, TLR signaling can be desinhibited through degradation of the extracellular matrix (27). In glioma this may lead to a vicious cycle in which TLRs induce metalloproteinase activity that in turn facilitates further TLR signaling.…”
Section: Glioma Cells Induce Microglial Mt1-mmp Expression Via Tlr Simentioning
confidence: 99%
“…Moreover, in vivo TLRs can also be stimulated by factors liberated after cell necrosis, which is a frequent event in high-grade gliomas. Additionally, TLR signaling can be desinhibited through degradation of the extracellular matrix (27). In glioma this may lead to a vicious cycle in which TLRs induce metalloproteinase activity that in turn facilitates further TLR signaling.…”
Section: Glioma Cells Induce Microglial Mt1-mmp Expression Via Tlr Simentioning
confidence: 99%
“…8 Tumor tissue destruction mediated by gefitinib and other chemotherapeutic agents likely produces endogenous Toll-like receptor (TLR) ligands, including hyaluronan and heparan sulfate. 9, 10 We recently reported that gefitinib administration to mice along with the exogenous TLR ligand lipopolysaccharide (LPS) or various endogenous ligands induces interstitial lung disease. 11 Mice treated with gefitinib and LPS showed elevated expression of the transcription factor Fos-related antigen-1 (Fra-1, encoded by Fosl1) in lung tissues.…”
Section: Introductionmentioning
confidence: 99%
“…This has already been tested in the case of immune stimulatory heparin sulphate (HS) fragments which are released from the ECM as a result of elastase activity (Brunn et al, 2005). Injection of elastase into the peritoneal cavity of mice caused the release of HS and induced sepsis, nearly as effectively as direct injection of HS or LPS (Johnson et al, 2004). Thus therapeutic measures aimed at…”
Section: Resultsmentioning
confidence: 99%